Respiratory infections in allergic children: the preventive role of a multicomponent nutraceutical - Zicari, Anna Maria; De Castro, Giovanan; Brindisi, Giulia; Papale, Maria; Marinelli, Guido; Licari, Amelia; Ciprandi, Giorgio (Acta Biomedica Atenei Parmensis, 2020)
Allergic children with respiratory infections (RI) are a demanding challenge for the paediatrician. Antibiotic prescription represents a critical problem, mainly concerning the growing issue of resistance. To prevent RI would be therefore a goal in clinical practice. In this regard, modulation of immune system may have a critical role. The aim of the present study was to measure the number of respiratory infections and the use of antibiotics in two groups of children suffering from allergic rhinoconjunctivitis. The first group took a course of a nutraceutical (Lertal®) before the observation (active group, AG); a second one was considered as control (control group, CG). The children were visited at baseline and after 1 year. The number of RI and of antibiotic courses was the primary outcomes. Children in AG reported a significant reduced number of RI and of antibiotic course in comparison with CG (p=0.01 and 0.002 respectively). In conclusion, the current study showed that a course with a multicomponent nutraceutical could reduce the number of respiratory infections and consequently the use of antibiotics in children with allergic rhinoconjunctivitis.